2021
DOI: 10.1080/2162402x.2020.1862529
|View full text |Cite
|
Sign up to set email alerts
|

Tumor immune infiltration estimated from gene expression profiles predicts colorectal cancer relapse

Abstract: A substantial fraction of patients with stage I-III colorectal adenocarcinoma (CRC) experience disease relapse after surgery with curative intent. However, biomarkers for predicting the likelihood of CRC relapse have not been fully explored. Therefore, we assessed the association between tumor infiltration by a broad array of innate and adaptive immune cell types and CRC relapse risk. We implemented a discovery-validation design including a discovery dataset from Moffitt Cancer Center (MCC; Tampa, FL) and thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
3
6
0
Order By: Relevance
“…Consistently, the gene expression profiles suggestive of immune infiltration appeared to be a predictor of dysfunctional T cell phenotypes and a worse prognosis of the cohort of those cancers. In agreement with our findings, previous studies indicated that NK (resting and activated) cell, monocyte, resting mast cell, neutrophil, M1 and M2 TAM, activated dendritic cell, CD4+ T cell, and CD8+ T cell infiltrations were significant predictors of disease relapse, even after accounting for known prognostic indicators, including adjuvant therapy [40].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistently, the gene expression profiles suggestive of immune infiltration appeared to be a predictor of dysfunctional T cell phenotypes and a worse prognosis of the cohort of those cancers. In agreement with our findings, previous studies indicated that NK (resting and activated) cell, monocyte, resting mast cell, neutrophil, M1 and M2 TAM, activated dendritic cell, CD4+ T cell, and CD8+ T cell infiltrations were significant predictors of disease relapse, even after accounting for known prognostic indicators, including adjuvant therapy [40].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the hub genes expression signatures of M2 TAMs are inversely associated with gene expression profiles suggestive of T cell exclusion phenotypes (Figure 6D), indicating that the hub genes are unlikely to play a role in macrophages dependent regulation of T cell exclusion phenotypes in the hub cancers. Conversely, the gene expression profiles suggestive of dysfunctional T cell phenotypes and high survival risk (Figure 6C) predicted in cohorts with high expression levels of the hub genes suggest the oncogenic role of Mo macrophages in these cancers, a conclusion supported by previous studies [40,42].…”
Section: Discussionsupporting
confidence: 74%
“…However, downregulation of these molecules is a common mechanism of immune evasion ( 6 ), albeit its correlation with tumour prognosis is not clear yet ( 7 ). For instance, NK cell infiltration has been associated with a lower risk of disease relapse in CRC ( 8 ). As a safeguard for T-cell function, NK cells control tumours that have reduced HLA-I expression and provide an activating balance of signals through surface receptors ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…mIF technologies allow for the use of multiple antibodies to achieve the simultaneous detection of several marker on single tissue sample (recently nine or more markers). This technology has been used in research and clinical settings showing the utility of this approach for studying the TIME [ 45 , 46 , 47 ]. An overview of the data generation process with mIF technology is presented in Figure 1 , focusing on cyclic-immunofluorescence and tyramide-based mIF.…”
Section: Data Preprocessing and Quality Control Of Mif Datamentioning
confidence: 99%
“…This is a labor-intensive procedure and may take several days to complete. However, fully automated staining protocols for mIF have been developed, saving time and improving staining variability [ 45 , 46 , 47 , 48 , 49 ].…”
Section: Data Preprocessing and Quality Control Of Mif Datamentioning
confidence: 99%